2008
DOI: 10.1152/japplphysiol.00541.2007
|View full text |Cite
|
Sign up to set email alerts
|

Wave reflection and central aortic pressure are increased in response to static and dynamic muscle contraction at comparable workloads

Abstract: Edwards DG, Mastin CR, Kenefick RW. Wave reflection and central aortic pressure are increased in response to static and dynamic muscle contraction at comparable workloads. J Appl Physiol 104: 439-445, 2008. First published December 13, 2007 doi:10.1152/japplphysiol.00541.2007.-We determined the effects of static and dynamic muscle contraction at equivalent workloads on central aortic pressure and wave reflection. At random, 14 healthy men and women (23 Ϯ 5 yr of age) performed a static handgrip forearm contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 38 publications
3
34
0
Order By: Relevance
“…The reasons for this are not entirely clear but are in line with some previous studies that have reported increases in AIx during forearm exercise (3,5,10), probably due to increased sympathetic activity. This contrasts with other studies of whole body exercise, which have typically reported decreased AIx during exercise (7,12,13).…”
Section: Discussionsupporting
confidence: 84%
“…The reasons for this are not entirely clear but are in line with some previous studies that have reported increases in AIx during forearm exercise (3,5,10), probably due to increased sympathetic activity. This contrasts with other studies of whole body exercise, which have typically reported decreased AIx during exercise (7,12,13).…”
Section: Discussionsupporting
confidence: 84%
“…Given the statistical relationship between MAP and AI in the present study, we speculate that the primary mechanism of increased wave reflection during facial cooling is alteration in the amplitude and site of wave reflections as a result of sympathetic activation. Previous observations of increased wave reflection during handgrip exercise (12) or CPT (17) may be due to the same mechanism.…”
Section: Discussionmentioning
confidence: 64%
“…During both high-intensity dynamic (Sharman et al 2005;Studinger et al 2003) and static exercise (Edwards et al 2008;Lydakis et al 2008a, b;Reid and Conway 2006), there are increases in central artery stiffness. Following acute dynamic exercise, there is a reduction in central artery stiffness with lower intensity exercise (Heffernan et al 2007a) but no change in central artery stiffness with maximal dynamic exercise (Heffernan et al 2007b, c).…”
Section: Discussionmentioning
confidence: 99%